LITERASI NUMERASI DAN REPRESENTASI MATEMATIS: STUDI PADA PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) CURIOSITY PESERTA DIDIK - Sindi Amelia; Bambang Sri Anggoro; Siti Ulfa Nabila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Indonesian Realistic Mathematics Education (PMRI) approach on numeracy literacy and mathematical representation abilities as viewed from students’ curiosity. This research uses a quasi-experimental method with a 2×2 factorial design. The population is class VII students of SMPN 1 Buay Madang, with samples selected using random sampling techniques. The instruments used are numeracy literacy tests, mathematical representation tests, and a curiosity questionnaire. Data analysis used two-way MANOVA. The results showed that the PMRI approach had a significant effect on students' numeracy literacy and mathematical representation abilities. Students' curiosity also affected both abilities. Furthermore, the interaction between PMRI and curiosity positively influenced students' abilities. These findings suggest that contextual learning through PMRI combined with high student curiosity improves students' mathematical understanding and skills. Therefore, it is recommended for mathematics educators to apply realistic and curiosity-stimulating learning approaches in the classroom.